A Gross‐Margin Model for Defining Technoeconomic Benchmarks in the Electroreduction of CO2. Issue 15 (27th June 2016) - Verma, Sumit; Kim, Byoungsu; Jhong, Huei‐Ru "Molly"; Ma, Sichao; Kenis, Paul J. A.
Abstract: We introduce a gross‐margin model to evaluate the technoeconomic feasibility of producing different C1 –C2 chemicals such as carbon monoxide, formic acid, methanol, methane, ethanol, and ethylene through the electroreduction of CO2 . Key performance benchmarks including the maximum operating cell potential ( V max ), minimum operating current density ( j min ), Faradaic efficiency (FE), and catalyst durability ( t catdur ) are derived. The V max values obtained for the different chemicals indicate that CO and HCOOH are the most economically viable products. Selectivity requirements suggest that the coproduction of an economically less feasible chemical (CH3 OH, CH4, C2 H5 OH, C2 H4 ) with a more feasible chemical (CO, HCOOH) can be a strategy to offset the V max requirements for individual products. Other performance requirements such as j min and t catdur are also derived, and the feasibility of alternative process designs and operating conditions are evaluated. Abstract : Can we reduce CO2 emissions and still make money? A gross‐margin‐based economic model is presented that identifies the technoeconomic benchmarks required for the economically viable electroreduction of CO2 to different C1 –C2 chemicals and fuels. The important factors that control the economics are evaluated, and a perspective on future research directions is presented.